Konsep Hard Skill, Soft Skill Dan Spiritual Skill Pustakawan Menghadapi Era Library 3.0 - Mohamad Rotmianto (Pustakaloka, 2015)
In  this  present  time,  librarian  must  know  well  about information technology or  it also called have a  literacy of  information technology.  Because  they  (librarian)  will  face  the  “explosion  of information”, as well as a new  library user named “Net Generation” who wants all information to be presented more accurate, quicker and interactively, as the demands of Library 3.0. Mastery three skills: hard skill  (IQ)  and  soft  skill  (EQ   )  combined  with  spiritual  skill  (SQ)  is required  to  succeed  to be a Librarian 3.0,  so not only qualifed  in  the feld of technology, but more than that librarians also have a humanism side that is based on religious principles.